"It is very difficult in this business if you want to have a good conscience": pharmaceutical governance and on-the-ground ethical labour in Ghana. Issue 1 (31st December 2022) - Hampshire, Kate; Mariwah, Simon; Amoako-Sakyi, Daniel; Hamill, Heather
ABSTRACT: The governance of pharmaceutical medicines entails complex ethical decisions that should, in theory, be the responsibility of democratically accountable government agencies. However, in many Low- and Middle-Income Countries (LMICs), regulatory and health systems constraints mean that many people still lack access to safe, appropriate and affordable medication, posing significant ethical challenges for those working on the "front line". Drawing on 18 months of fieldwork in Ghana, we present three detailed case studies of individuals in this position: an urban retail pharmacist, a rural over-the-counter medicine retailer, and a local inspector. Through these case studies, we consider the significant burden of "ethical labour" borne by those operating "on the ground", who navigate complex moral, legal and business imperatives in real time and with very real consequences for those they serve. The paper ends with a reflection on the tensions between abstract, generalised ethical frameworks based on high-level principles, and a pragmatic, contingent ethics-in-practice that foregrounds immediate individual needs – a tension rooted in the gap between the theory and the reality of pharmaceutical governance that shifts the burden of ethical labour downwards and perpetuates long-term public health risks.